Occupational Therapy Practice Guidelines for People With Parkinson’s Disease. - Wood, Julia; Henderson, Whitney; Foster, Erin R. (American Journal of Occupational Therapy)
Importance: Occupational therapy practitioners address the occupational performance and participation needs of people with Parkinson’s disease (PD) and their care partners. Objective: This Practice Guideline is informed by systematic reviews on the use of occupational therapy interventions to promote participation in occupations for people with PD and to facilitate their caregivers’ participation in the caregiver role. This guideline is meant to support practitioners’ clinical decision making when working with people with PD and their care partners. Method: We examined and synthesized the results of four systematic reviews and integrated those results into clinical recommendations for practice. Results: Thirty-three articles from the systematic reviews served as the basis for the clinical recommendations in this Practice Guideline. Clinical recommendations are provided for interventions that have strong or moderate supporting evidence. Conclusion and Recommendations: Multidisciplinary, tailored, goal-oriented intervention is recommended for people with PD. Various forms of exercise can be used to improve activities of daily living and instrumental activities of daily living performance and social participation, and interventions should incorporate health behavior change techniques to support adequate physical activity levels in daily life. Mindfulness meditation and exercise can be used to support sleep, and task-oriented training can be used to improve performance of specific tasks. Occupational therapy practitioners should incorporate self-management, coaching, compensatory, cognitive–behavioral, and other approaches into multicomponent treatment plans depending on the client’s needs and goals. Additional potentially appropriate intervention approaches or areas to address are discussed on the basis of existing or emerging evidence and expert opinion. What This Article Adds: This Practice Guideline provides a summary and applications of the current evidence supporting occupational therapy intervention for people with PD. It includes case examples and suggested decision-making algorithms to support practitioners in addressing client goals.